EMPLOYED WOMEN WHO GO IN FOR SPORTS - SATISFACTION WITH ONESELF, ONE'S FAMILY, ONE'S JOB, ONE'S SOCIAL LIFE AND GENERAL LIFE SATISFACTION - Nina Brkić; Svetlana Kalabić (Exercise and Quality of Life)
Health care professionals consider awareness of benefits of physical activities and exercise to be of the utmost importance in health promotion. Lack of physical activity amongst employees is one of the predisposing factors contributing to obesity and a risk factor for numerous illnesses and non-advancement in job. The main objective of this research is to explore the connection between physical activities in employed women and satisfaction with oneself, one's family, one's job, one's social life and general life satisfaction. A survey was conducted amongst 300 employed women, 160 of whom do not go in for sports while 140 of them do. The findings show that the women who go in for sports are considerably more satisfied with themselves and their family compared to those who do not go in for sports. Significant differences are also related to job satisfaction and social life as well as general life satisfaction.